2012
DOI: 10.1111/j.1365-2044.2011.06989.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nitrous oxide on intra‐ocular pressure in healthy adults*

Abstract: SummaryMany anaesthetic agents affect intra-ocular pressure, yet little is known about nitrous oxide and intra-ocular pressure. This study assessed the effect of nitrous oxide on intra-ocular pressure in 20 healthy adult volunteers. The intra-ocular pressure was measured at baseline, while breathing a 70:30 mix of nitrous oxide and oxygen for 12 min, and then while breathing room air for 15 min. A linear mixed effects model was used to assess change in intra-ocular pressure over time. There was no significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Lalwani et al have shown that nitrous oxide inhalation did not significantly change IOP from baseline values in a population of healthy adults [13]. Our result of present study was consistent with their result.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Lalwani et al have shown that nitrous oxide inhalation did not significantly change IOP from baseline values in a population of healthy adults [13]. Our result of present study was consistent with their result.…”
Section: Discussionsupporting
confidence: 83%
“…Based on the present and previous similar study [11]- [13], the effect of N 2 O would not affect the IOP during 3 hours sevoflurane and remifentanil anesthesia in patients undergoing abdominal surgery. Our study had the following possible limitations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…I read with interest the recent article by Lalwani et al demonstrating that nitrous oxide (N 2 O) did not significantly change intra‐ocular pressure (IOP) from baseline in healthy adults [1]. The authors concluded that this raises the possibility of using N 2 O to aid IOP measurement, either as a sole inhalational agent or as part of a multi‐agent protocol.…”
mentioning
confidence: 99%